2011 IEEE International Conference on Robotics and Biomimetics 2011
DOI: 10.1109/robio.2011.6181694
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion modes for a hybrid wheeled-leg planetary rover

Abstract: This paper introduces locomotion modes for the planetary rover Sherpa 1 . The rover's locomotion system consists of four wheeled-legs, each providing a total of six degrees of freedom. The design of the active suspension system allows a wide range of posture and drive modes for the rover. Selflocking gears in the suspension system allow to maintain the body height without the need of actively driving the actuators. Thus, energy-efficient wheeled locomotion and at the same time high flexibility in ground adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…In recent years, on the other hand, rovers with active chassis, or redundant mobility in their locomotion mechanism, have attracted considerable attention for their application to space exploration, for example the Sample Return Rover (Schenker et al., , ), ATHLETE (Wilcox et al., ), Scarab (Wettergreen et al., ), Tri‐star IV (Aoki et al., ), and Sherpa (Cordes et al., ). Such rovers are able to actively modify their configuration to adapt to rough environments, and several studies so far have shown their potential to negotiate challenging terrain.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, on the other hand, rovers with active chassis, or redundant mobility in their locomotion mechanism, have attracted considerable attention for their application to space exploration, for example the Sample Return Rover (Schenker et al., , ), ATHLETE (Wilcox et al., ), Scarab (Wettergreen et al., ), Tri‐star IV (Aoki et al., ), and Sherpa (Cordes et al., ). Such rovers are able to actively modify their configuration to adapt to rough environments, and several studies so far have shown their potential to negotiate challenging terrain.…”
Section: Introductionmentioning
confidence: 99%
“…SherpaTT is the successor of the system Sherpa (Cordes, Dettmann, & Kirchner, ) improving the workspace of the legs while having a reduced number of active DoF (Cordes et al, ). Both Sherpa‐versions are designed to work together with other robots in unstructured terrain; while Sherpa has to transport a highly mobile six‐legged walking robot (Roehr et al, ), SherpaTT has to transport immobile payloads requiring higher flexibility in the rover’s body pose control for deployment and pick‐up.…”
Section: Sherpatt: System Overviewmentioning
confidence: 99%
“…An ICR in infinity of the y ‐axis of the SCS corresponds to a pure forward movement, while positioning the ICR at the origin of the SCS results in a pure point turn of the robot. In Cordes et al (), an explicit calculation of the wheel orientation and wheel velocity for a rover with variable footprint is presented for the system Sherpa. The calculation assumes quasi‐static states and neglects the current movement of the suspension system.…”
Section: Control System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Sherpa makes use of an active suspension system that allows to select from a set of locomotion modes depending on the current terrain situation. These modes range from various postures to enhance the relationship between the center of gravity and the center of the support polygon to substantially different drive modes, for example planar omnidirectional movements or inchworming modes (Cordes et al., ). Figure displays the final state of the integration of Sherpa.…”
Section: Rimres – a System Of Systemsmentioning
confidence: 99%